La calidad del producto y servicio al cliente que oferta El Patron Drink Coctails ubicado en Bajo Alto El Guabo. - Velez Romero, Cristhian Josue (My University, 2021)
Product quality and customer service is of utmost importance within an establishment, therefore, the purpose of this study focuses on investigating the acceptance of both terms in the simple context that summarizes what quality is "knowing how to do things well ”. For this reason, both diners and / or customers who consume and have a perception of both this establishment and what it offers will be consulted, it is still an innovative proposal with a significance already of almost a year 6 months, and in response to tourism both sender and receiver, without leaving aside what is currently being experienced with the onset of the pandemic. The present study proposes as objectives, to examine the level of acceptance of diners and / or clients towards the establishment and what it offers, to determine those elements that are positive and negative in relation to the perceived quality of service, to make use of the basic concepts and recommendations on improving product quality and customer service. On the other hand, this project will have a research process that will respond to the general objective and in turn to a structure comprised of three chapters, conclusions and recommendations. In Bajo Alto there are various establishments of second-rate bars as described in the registry of the Ministry of Tourism, for this reason it is that, appreciating it from the perspective of a market, there are offers to satisfy demands, which represent profitability for the inhabitants of this destination and the visitors, likewise the high value or significance that means "quality services and customer service" adapting the spaces with music, giant screens to appreciate videos or enjoy karaoke with friends, events, live shows, among others, being a plus that contributes to the movement of the economy of the local inhabitants. The importance of this research work is specifically aimed at contributing to the improvement of both the establishment, the offer and the quality of customer service, to emphasize these aspects it must be taken into account that due to the characteristic of what for professionals and future professionals of the branch of the Hospitality and Tourism Administration is precisely what is intangible and tangible of these, only in this way will it be possible to contribute to the improvement of the space, through the use of promotion and dissemination, as well as what will lead to this point and others will be the application of surveys that will yield results that when processed will allow the author to make constructive recommendations. If we go to a bar establishment, it is where the client can consume alcoholic and non-alcoholic beverages according to what they are ready to consume, the collaborators must provide excellent attention and kindness to satisfy the needs of the same. A very important point must be taken into account and nowadays every company needs innovation, which has become essential for every company, since in this way it will be able to stay in the competitive market and in turn, give a touch different from your final product.
La calidad del producto y el servicio al cliente es de suma importancia dentro de un establecimiento, debido a ello, la finalidad del presente estudio se centra en la investigación, aceptación de ambos términos permitiendo la optimización de procesos y el logro de los objetivos propuestos. Determinando aquellos elementos que resulten positivos o negativos en relación a la calidad de servicio percibida, haciendo uso de los conceptos básicos y las recomendaciones para el mejoramiento de la calidad del producto y el servicio al cliente. La importancia del presente trabajo de investigación, está orientado específicamente en el mejoramiento del establecimiento Bar, su oferta y la calidad del servicio al cliente. Como futuros profesionales dentro la rama de la Administración de Hotelería y Turismo, es determinante encontrar en la presente indagación científica lo intangible y tangible de estos, para de esta forma contribuir en el mejoramiento de este tipo de negocios, destacando el buen uso, promoción y difusión, de estrategias de atención al cliente. Ello sumado a la aplicación de diversos instrumentos, permitirá por medio del autor plantear recomendaciones constructivas que maximicen las potencialidades de estos negocios como de sus respectivos destinos turísticos. En Bajo Alto existen diversos establecimientos de Bares de segunda categoría como lo describe el catastro del Ministerio de Turismo, por ello es que apreciándolo desde la óptica de un mercado hay ofertas para satisfacer demandas, mismas que representan rentabilidad para los habitantes de este destino y los visitantes, así mismo el alto valor o significancia que significa “servicios de calidad y atención al cliente” adecuando los espacios con música, pantallas gigantes para apreciar videos o disfrutar de un karaoke entre amigos, eventos, shows en vivo, entre otros, siendo un plus que coadyuva al movimiento de la economía de los habitantes locales. La importancia de este trabajo de investigación, se orienta específicamente a contribuir en la mejora tanto del establecimiento, la oferta y la calidad del servicio al cliente, para hacer énfasis en estos aspectos se debe tener en cuenta que por la característica de lo que para los profesionales y futuros profesionales de la rama de la Administración de Hotelería y Turismo es justamente lo intangible y tangible de estos, solo así se podrá contribuir para el mejoramiento del espacio, por el uso de la promoción y difusión, así mismo lo que conducirá a este punto y demás será la aplicación de encuestas que arrojarán resultados que al ser procesados permitirá al autor plantear recomendaciones constructivas. Si direccionamos a un establecimiento de bar, es donde el cliente puede consumir bebidas alcohólicas y no alcohólicas según lo que estén prestos a consumir, los colaboradores deben brindar una excelente atención y amabilidad para satisfacer las necesidades del mismo. Hay que tomar en cuenta un punto muy importante y hoy en día toda empresa necesita de ello, la innovación, misma que se ha vuelto indispensable para toda empresa, ya que de esa forma podrá mantenerse en el mercado competitivo y a su vez, dar un toque diferente a su producto final.
Keywords: CALIDAD DE SERVICIO; ATENCIÓN AL CLIENTE; PRODUCTO; OFERTA; DEMANDA